2017
DOI: 10.1111/1477-8947.12122
|View full text |Cite
|
Sign up to set email alerts
|

An Environmental Kuznets Curve for N2O emissions in Germany: an ARDL approach

Abstract: This paper analyses the relationship between nitrous oxide (N 2 O) emissions, economic growth, agricultural land used and exports in Germany. We use time-series data between 1970 and 2012 and the Autoregressive Distributed Lag (ARDL) methodology to test for cointegration in the long run. Results show that there is a quadratic long run relationship between N 2 O emissions and economic growth, confirming the existence of an Environmental Kuznets Curve (EKC) for Germany. Agricultural land area affects N 2 O emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 51 publications
2
22
1
Order By: Relevance
“…GDP is also one of the important determinants of environmental quality. Zambrano-Monserrate and Fernandez [46] observed that increased GDP due to the technique effect led to a quadratic association between income and N 2 O emissions by validating the EKC hypothesis. Moreover, Copeland and Taylor [47] and Chang [48] observed that if economic growth came through trade openness, then environmental quality deteriorated with economic growth, and eventually such scale effect of income was offset by the technological changes due to changes in preferences of the people [49].…”
Section: Literature Reviewmentioning
confidence: 70%
“…GDP is also one of the important determinants of environmental quality. Zambrano-Monserrate and Fernandez [46] observed that increased GDP due to the technique effect led to a quadratic association between income and N 2 O emissions by validating the EKC hypothesis. Moreover, Copeland and Taylor [47] and Chang [48] observed that if economic growth came through trade openness, then environmental quality deteriorated with economic growth, and eventually such scale effect of income was offset by the technological changes due to changes in preferences of the people [49].…”
Section: Literature Reviewmentioning
confidence: 70%
“…Poverty and reduction of ecological assets are highly coupled in rural China (Cao et al, 2015). Some case studies showed that the economic development and environment follow the inverted U shape of the environmental Kuznets Curve (Hassan et al, 2015; Zambrano‐Monserrate and Fernandez, 2017; Wang and Shen, 2016; Mao et al, 2013; Li et al, 2016; Zhang et al, 2015a).…”
Section: Discussionmentioning
confidence: 99%
“…[54][55][56][57] The most widely used single indicator for environmental pollution is CO 2 emission. 58 As an alternative to CO 2 emission, a wide variety of single measure indicators have been used to represent environmental damage, such as nitrogen dioxide (NO 2 ), 59,60 sulfur dioxide (SO 2 ), [61][62][63] industrial waste, 64 water pollution, 65 threatened species, 66 and deforestation. 67 There are also studies that use several single variables to enhance the context of the research.…”
Section: Literature Reviewmentioning
confidence: 99%